2006
DOI: 10.1002/macp.200500406
|View full text |Cite
|
Sign up to set email alerts
|

Zirconocene Propylene Polymerisation: Controlling Termination Reactions

Abstract: Summary: Propylene was polymerised at varying trimethylaluminium (TMA) concentration with two metallocenes activated by methylaluminoxane (MAO) in an attempt to better understand the effect of TMA on the activation process, catalyst activity and termination reactions. A chemical treatment of MAO solution with 2,6‐di‐tert‐butyl‐p‐cresol was used to obtain TMA‐free polymerisation conditions. The metallocene precursors under investigation were diphenylmethyl(cyclopentadienyl)(9‐fluorenyl)zirconium dichloride (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…While TMA has been shown to monoalkylate dichloride catalyst precursor, [7e13] its role in the activation process itself is elusive. Usually TMA is found to reduce the activity of the catalysts, [7e11] but addition of TMA has also been reported to increase the activity, [14,15] or even to act as the actual cocatalyst [4,15]. A number of related computational studies have been reported on aspects concerning ligand abstraction, ion pair formation and monomer incorporation with various cocatalysts and catalyst precursors [10,13,16e25].…”
Section: Introductionmentioning
confidence: 99%
“…While TMA has been shown to monoalkylate dichloride catalyst precursor, [7e13] its role in the activation process itself is elusive. Usually TMA is found to reduce the activity of the catalysts, [7e11] but addition of TMA has also been reported to increase the activity, [14,15] or even to act as the actual cocatalyst [4,15]. A number of related computational studies have been reported on aspects concerning ligand abstraction, ion pair formation and monomer incorporation with various cocatalysts and catalyst precursors [10,13,16e25].…”
Section: Introductionmentioning
confidence: 99%
“…In the monomer-starved polymerization system, chain transfer with cocatalyst (AlEt 3 in this work) may become the dominant termination reaction in the absence of hydrogen [6,14,24,25], as the AlEt 3 concentration will be much higher than [M]. As reported in literatures, the product of transfer with alkylaluminum, the aluminum-terminated PP chains, can be converted to hydroxyterminated PP chains after quenching the polymerization system with oxygen and subsequent hydrolysis [24,25].…”
Section: Suppression Of Chain Transfer To Cocatalystmentioning
confidence: 88%
“…Since the 1990s, chain transfer reactions in olefin polymerization with metallocene catalysts have been studied in detail [4][5][6][7][8][9][10][11][12][13]. However, study of chain transfer reactions in MgCl 2 -supported catalyst systems was limited, partly because of the difficulties in tracing the low level of active sites in these heterogeneous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there have also been several studies of alane chain transfer in fluorenyl‐ and Cp‐based zirconocene‐mediated propylene polymerization systems 8a,c,d. These studies again indicate that addition of AlMe 3 or excess MAO to the polymerization processes results in depressed product polymer M n values along with polymer microstructures containing saturated isopropyl end groups, suggesting alane chain transfer as the dominant chain‐termination pathway.…”
Section: Alane Chain Transfer (Chain Transfer To Aluminum)7–12mentioning
confidence: 91%